Design and Exploratory Implementation of a Mobile Scratch-Based Learning Tool to Foster Computational Thinking in Elementary Students - Fachlevi, Riyan Syah; Ali, Mahrus; Romadhon, Muhammad Imron (DIKODA JURNAL PENDIDIKAN SEKOLAH DASAR, 2026)
This study presents the design and exploratory implementation of a mobile (Android-based) Scratch project learning tool aimed at supporting elementary students’ computational thinking (CT) in informal educational settings. Grounded in constructionist learning theory, the research addresses gaps in accessibility and pedagogical design identified in prior Scratch-CT studies, particularly the lack of validated assessment instruments and limited focus on mobile/informal contexts. Using the ADDIE model, a prototype was developed and validated by experts, then trialed with 10 fifth-grade students in an after-school program. Student engagement and demonstration of CT indicators (decomposition, pattern recognition, abstraction, algorithmic thinking, debugging, sequencing) were observed using a structured checklist. While students showed increased engagement and some evidence of CT skill development, findings are preliminary due to the small sample, short duration, and reliance on non-standardized observation. The study offers a framework for future research on mobile CT learning and highlights the need for rigorous, validated assessment in this domain.